Biomechanical analysis of serving technique in table tennis for Yining Zhang: Elite female player - Wang, J.; Li, J.; Liang, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: High-quality serving techniques can control an opponent, create opportunities for attacking and even score directly. Therefore, according to the biomechanical analysis of service techniques for Yining Zhang, who is ranked as the top female player in world women's table tennis (2007), this study can enrich the body of theories related to table tennis skills. Study findings will also provide a reference for sports scientists and coaches for table tennis training.